A Critical Review of Kaempferol in Intestinal Health and Diseases - Jun Chen; Haopeng Zhong; Zhouyin Huang; Xingping Chen; Jinming You; Tiande Zou (MDPI AG, 2023)
Kaempferol, a secondary metabolite found in plants, is a naturally occurring flavonoid displaying significant potential in various biological activities. The chemical structure of kaempferol is distinguished by the presence of phenyl rings and four hydroxyl substituents, which make it an exceptional radical scavenger. Most recently, an increasing number of studies have demonstrated the significance of kaempferol in the regulation of intestinal function and the mitigation of intestinal inflammation. The focus of the review will primarily be on its impact in terms of antioxidant properties, inflammation, maintenance of intestinal barrier function, and its potential in the treatment of colorectal cancer and obesity. Future research endeavors should additionally give priority to investigating the specific dosage and duration of kaempferol administration for different pathological conditions, while simultaneously conducting deeper investigations into the comprehensible mechanisms of action related to the regulation of aryl hydrocarbon receptor (AhR). This review intends to present novel evidence supporting the utilization of kaempferol in the regulation of gut health and the management of associated diseases.